Knowledge, Attitudes, and Practices Regarding Contraception Among Young Women in Urban Indonesia: A Mixed-Methods Approach - Hidayat, Rachmat; Cinthya Callathea; Taufiq Indera Jayadi; Maximillian Wilson (Sriwijaya Journal of Obstetrics and Gynecology, 2024)
Introduction: Unintended pregnancies and unsafe abortions remain significant public health concerns in Indonesia, particularly among young women in urban areas. This study aimed to explore the knowledge, attitudes, and practices (KAP) regarding contraception among young women residing in urban Indonesia, employing a mixed-methods approach to gain an in-depth understanding of this complex issue. Methods: This study used a sequential explanatory mixed-methods design. The quantitative phase involved a cross-sectional survey of 500 young women aged 18-24 years residing in Jakarta, Indonesia. A structured questionnaire assessed their knowledge about various contraceptive methods, attitudes towards contraception, and current contraceptive practices. The qualitative phase comprised in-depth interviews with 30 participants purposively selected from the survey sample to explore their experiences, beliefs, and perspectives on contraceptive use. Quantitative data were analyzed using descriptive statistics and logistic regression, while thematic analysis was employed for qualitative data. Results: The quantitative findings revealed that while the majority of participants had good knowledge about contraception, misconceptions and gaps existed regarding specific methods, particularly long-acting reversible contraceptives (LARCs). Attitudes towards contraception were generally positive, although concerns about side effects and social stigma were prevalent. The prevalence of current contraceptive use was moderate, with condoms and oral contraceptive pills being the most common methods. Qualitative findings provided deeper insights into the factors influencing contraceptive use, including perceived susceptibility to pregnancy, partner communication, family and social influences, access to healthcare services, and religious beliefs. Conclusion: This study highlights the need for comprehensive sexuality education programs tailored to address misconceptions and promote informed decision-making about contraception among young women in urban Indonesia. Strategies to improve access to youth-friendly contraceptive services and address social and cultural barriers to contraceptive use are also essential.